2002
DOI: 10.1111/j.1746-1561.2002.tb07917.x
|View full text |Cite
|
Sign up to set email alerts
|

Youth Risk Behavior Surveillance — United States, 2001

Abstract: Priority health-risk behaviors, which contribute to the leading causes of mortality and morbidity among youth and adults, often are established during youth, extend into adulthood, are interrelated, and are preventable. This report covers data during February-December 2001. The Youth Risk Behavior Surveillance System (YRBSS) monitors six categories of priority health-risk behaviors among youth and young adults; these behaviors contribute to unintentional injuries and violence; tobacco use; alcohol and other dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
440
9
26

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 517 publications
(504 citation statements)
references
References 2 publications
29
440
9
26
Order By: Relevance
“…More than a third of adolescents in grades 9 to 12 do not regularly participate in vigorous physical activity (Grunbaum et al, 2004; National Association for Sport and Physical Education & American Heart Association, 2006). Whereas, over 11% of the more than 15,000 high school students surveyed for the 2003 National Youth Risk Behavior Survey, reported no moderate to vigorous physical activity (Grunbaum et al, 2004). Overall, among high school students, males are more physically active than females (Grunbaum et al, 2004; National Association for Sport and Physical Education & American Heart Association, 2006).…”
Section: Vigorous Physical Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…More than a third of adolescents in grades 9 to 12 do not regularly participate in vigorous physical activity (Grunbaum et al, 2004; National Association for Sport and Physical Education & American Heart Association, 2006). Whereas, over 11% of the more than 15,000 high school students surveyed for the 2003 National Youth Risk Behavior Survey, reported no moderate to vigorous physical activity (Grunbaum et al, 2004). Overall, among high school students, males are more physically active than females (Grunbaum et al, 2004; National Association for Sport and Physical Education & American Heart Association, 2006).…”
Section: Vigorous Physical Activitymentioning
confidence: 99%
“…Whereas, over 11% of the more than 15,000 high school students surveyed for the 2003 National Youth Risk Behavior Survey, reported no moderate to vigorous physical activity (Grunbaum et al, 2004). Overall, among high school students, males are more physically active than females (Grunbaum et al, 2004; National Association for Sport and Physical Education & American Heart Association, 2006).…”
Section: Vigorous Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…3,5 Data from CDC's 2003 Youth Risk Behavior Survey indicated that fewer than 22% of high school students consumed the recommended 5 or more servings/day of fruits and vegetables. 6 Meeting the public health recommendations for these four health risk behaviors is expected to improve quality of life and reduce considerably the incidence of obesity and several chronic diseases. 2,7,9 Despite extensive evidence about the high prevalence of risk behaviors, little is known about the relationship among these behaviors, such as their clustering patterns, especially in adolescents.…”
Section: Introductionmentioning
confidence: 99%